Про згортки на просторах конфігурацій. ІІ. Простори локально скінченних конфігурацій - Фінкельштейн, Д.Л. (Український математичний журнал, 2012)
Рассмотрена свертка вероятностных мер на пространствах локально конечных конфигураций (подмножеств фазового пространства) и их связь со свертками соответствующих корреляционных мер и корреляционных функционалов, а также свертка гиббсовских мер. Исследована связь инвариантных мер относительно некоторого оператора и свойства соответствующего образа этого оператора на корреляционных функциях. We consider the convolution of probability measures on spaces of locally finite configurations (subsets of a phase space) and their connection with the convolution of the corresponding correlation measures and functionals. In particular, the convolution of Gibbs measures is studied. We also describe a relationship between invariant measures with respect to some operator and properties of the corresponding image of this operator on correlation functions.